A STUDY OF THE ATOMIZATION PROCESS USING NUMERICAL SIMULATION (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The liquid droplets atomization process plays an important role in several industrial processes and in many aspects of the combustion engines performance, gas turbines, diesel engines and rocket motors. The use of Computational Fluid Dynamics (CFD) to study the atomization process is relatively new and this work studies the atomization spray field using pressure swirl atomizers and the computation simulations was done by the using of the commercial software CFX 15. The parameter analyzed was the semi-angle of the spray. Particles were placed at the entrance and different settings for the primary and secondary breakup were studied. Two models for the primary breakup (BLOB and LISA models) were tested and two other for the secondary breakup (Reitz and Diwakar model and TAB model). The numerical results were compared with experimental data and showed acceptable compatibility.